Impact of Educational Gardens and Workshop Activities on 8th-Grade Student's Perception and Knowledge of Plant Biology - Herlander Azevedo; Isabel Soares-Silva; Fernando Fonseca; Paulo Alves; Duarte Silva; Maria-Manuel Azevedo (MDPI AG, 2022)
Educational gardens can be a significant resource in the promotion of environmental education, engaging both the school population and the general public. The main goal of the present study was to implement and assess a hands-on interventional program to promote knowledge and awareness of plant-related topics at a basic school level. We report on a hands-on educational project implemented with 8th-grade Portuguese students (mostly 13-14 years of age), associated with the establishment, on school grounds, of three educational gardens representing distinct Portuguese ecosystems. This was a collaborative project and encompassed several activities and subjects, including garden creation, plant propagation and plant care, plant identification, the study of form-function relationships, and lectures by plant researchers. A survey instrument with pre- and post-test assessments demonstrated the effectiveness of the program in raising student knowledge and awareness on topics centered around the native flora. Specifically, we noted that scores increased in all questions addressing different plant biology-related topics in the post-test assessment. This study supports the benefits of incorporating field/laboratory work and educational gardens in educational programs geared toward plant-oriented environmental education.